Selected Abstracts of the 20th National Congress of the Italian Society of Perinatal Medicine (Società Italiana di Medicina Perinatale, SIMP); Catania (Italy); March 22-24, 2018; Session “New Frontiers in Perinatal Medicine” - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2018)
20th National Congress of the Italian Society of Perinatal Medicine (Società Italiana di Medicina Perinatale, SIMP) Catania (Italy) • March 22nd-24th, 2018 SIMP PRESIDENT Irene Cetin CONGRESS PRESIDENTS Nicola Chianchiano, Angela Motta SCIENTIFIC COMMITTEE Mariarosaria Di Tommaso, Gianpaolo Donzelli, Luca Ramenghi ---------- Guest Editors: Irene Cetin, Nicola Chianchiano, Angela Motta ---------- Session “New Frontiers in Perinatal Medicine” ABS 1. CLINICAL AND METABOLIC OUTCOMES IN PREGNANT WOMEN AT RISK FOR GDM SUPPLEMENTED WITH MYO-INOSITOL. A SECONDARY ANALYSIS FROM 3 RCTS • A. Santamaria, A. Alibrandi, A. di Benedetto, B. Pintaudi, F. Corrado, F. Facchinetti, R. d’Anna ABS 2. PRE AND POST-NATAL CEREBRAL HEMODYNAMICS: CORRELATION WITH BIRTH WEIGHT, BASE ACID BALANCE AND NEONATAL OUTCOME • D. Buca, F. D’Antonio, F. Fanfani, S. Gustapane, M. Leombroni, L. Di Tizio, A. Ricciardulli, M. Liberati ABS 3. ROLE OF GLYCEMIC CONTROL IN THE DEVELOPMENT OF PREECLAMPSIA IN DIABETIC WOMEN • S. Ottanelli, C. Serena, S. Simeone, M.P. Rambaldi, F. Mecacci ABS 4. MATERNAL NUTRITION AND LIFESTYLE AS PREDICTORS OF PLACENTAL FUNCTION IN THE FIRST TRIMESTER OF PREGNANCY • I. di Bartolo, F. Parisi, C. Melinte, I. Cetin ABS 5. ADHERENCE TO MEDITERRANEAN DIET, WEIGHT GAIN AND THICKNESS SKINFOLD IN NORMAL WEIGHT PREGNANT WOMEN WITH OR WITHOUT GESTATIONAL DIABETES MELLITUS • A. Spadafranca, S. Digiacomo, A. Battezzati, S. Bertoli, I. Cetin, E. Ferrazzi ABS 6. THE ROLE OF ULTRASONOGRAPHY IN PRENATAL DIAGNOSIS OF CONGENITAL VASCULAR ANOMALIES • T. Izzo, S. Faiola, M. Lanna, L. Spaccini, E. Cattaneo, V. Baraldini, A. Turri, M.A. Rustico ABS 7. THREE-DIMENSIONAL AUTOMATED MEASURE OF THE FETAL THIGH IN HIGH-RISK PREGNANCIES TO PREDICT FETAL WEIGHT • T. Izzo, E. Ferrazzi, A. Farina, S. Rigano, V. Signorelli, M. Elisabetta, F. Fusè, D. Di Martino ABS 8. IMPACT OF BLADDER FILLING ON UTERINE ARTERY BLOOD FLOW INDICES IN THE FIRST TRIMESTER OF PREGNANCY • E. Magro Malosso, V. Seravalli, C. Morelli, L. Pasquini , G. Masini, M. Di Tommaso, F. Petraglia ABS 9. 17-BETA ESTRADIOL IN OBESE PREGNANCIES • G.M. Anelli, M.I. Mazzocco, T. Letizia, C. Novielli, T. Vago, C. Mandò, I. Cetin ABS 10. EARLY LABOR CEREBROPLACENTAL RATIO ASSESSMENT IN UNCOMPLICATED TERM PREGNANCIES AND PREDICTION OF ADVERSE PERINATAL OUTCOMES: A MULTICENTRE STUDY • A. Dall’Asta, T. Ghi, G. Rizzo, A. Cancemi, F. Aloisio, D. Arduini, G. Pedrazzi, F. Figueras, T. Frusca ABS 11. UMBILICAL CORD MANAGEMENT IN INFANTS BORN THROUGH ELECTIVE CESAREAN SECTION: COMPARISON OF THREE DIFFERENT METHODS • B. Galeazzo, S. Madella, B. Zanin, S. Visentin, D. Trevisanuto ABS 12. MATERNAL AND EMBRYO’S MTHFR GENOTYPES INFLUENCE THE RISK OF SPONTANEOUS ABORTION • R. Capucci, O. Brasile, A. Graziano, A. Poggi, R. Bassi Andreasi, V. Aleotti, A. Ravaei, M. Faisal Khan, V. Aiello, G. Astolfi, M. Rubini ABS 13. PREGESTATIONAL DIABETES IMPAIRS FETAL HEART RATE IN THE FIRST TRIMESTER OF PREGNANCY • A. Sirico, L. Sarno, M. Di Cresce, P. Martinelli, F. Zullo, G.M. Maruotti ABS 14. THE USE OF COMPUTERIZED CARDIOTOCOGRAPHY IN THE MANAGEMENT OF LATE INTRAUTERINE GROWTH RESTRICTED AND SMALL FOR GESTATIONAL AGE FETUSES • E. Riviello, S. Visentin, A. Londero, M. Andolfatto, M. Giannone, M. Camerin, E. Cosmi ABS 15. POSTPARTUM UNCONSCIOUS DYNAMICS EMERGING FROM THE LÜSCHER COLOR TEST IN MIGRANT WOMEN • L. Giliberti, G. Soldera, F. Volpe, C. Gentile, L. Severino, G. Straface, V. Zanardo ABS 16. RANDOMISED ITALIAN SONOGRAPHY FOR OCCIPUT POSITION TRIAL ANTE VACUUM (R.I.S.POS.T.A.) • T. Ghi, A. Dall’Asta, B. Masturzo, B. Tassis, M. Martinelli, N. Volpe, F. Prefumo, G. Rizzo, G. Pilu, L. Cariello, L. Sabbioni, A. Morselli-Labate, T. Todros, T. Frusca ABS 17. RISK FACTORS VERSUS CLINICAL OUTCOMES IN GDM PREGNANCIES • F. Basile, A. Alibrandi, L. Rizzo, G. Graffeo, L. Giunta, F. Corrado, A. Di Benedetto, R. D’Anna ABS 18. MODERATELY PROTEIN-RESTRICTED, PLANT-BASED SUPPLEMENTED DIETS IN PREGNANT CHRONIC KIDNEY DISEASE (CKD) PATIENTS: EFFECT ON UTERO-PLACENTAL DOPPLER FLOWS AND FETAL GROWTH • B. Montersino, F. Minelli, F. Fassio, F. Leone, L. Colla, M.M. Rossetti, G.B. Piccoli, R. Attini, T. Todros ABS 19. WNT ANTAGONIST SCLEROSTIN AND DICKKOPF-1 IN GESTATIONAL DIABETES • A. Catalano, B. Pintaudi, N. Morabito, L. Giunta, S. Loddo, F. Corrado, R. D’Anna, A. Lasco, A. Di Benedetto ABS 20. RISK FACTORS FOR ABNORMALLY INVASIVE PLACENTA: A SYSTEMATIC REVIEW AND META-ANALYSIS • D. Buca, M. Leombroni, A. Iacovelli, M. Liberati, M. Milani, M.E. Flacco, L. Manzoli, F. Fanfani, G. Calì, A. Familiari, G. Scambia, F. D’Antonio ABS 21. AN UNUSUAL CARDIAC COURSE OF RECIPIENT TWIN IN TWIN-TO-TWIN TRANSFUSION SYNDROME • M. Lucente, V. Comito, M. Salvia, G. Nigro, E. Bonanno, G. Scarpelli ABS 22. INFLUENCE OF PRENATAL DIAGNOSIS OF ABNORMALLY INVASIVE PLACENTA ON MATERNAL OUTCOME: A SYSTEMATIC REVIEW AND META-ANALYSIS • D. Buca, M. Liberati, G. Calì, F. Forlani, C. Caisutti, G. Pavone, M.E. Flacco, L. Manzoli, A. Familiari, G. Scambia, F. D’Antonio ABS 23. VEGAN-VEGETARIAN DIET ROLE IN IMPROVING FOETAL GROWTH AND AVOIDING DIALYSIS IN PREGNANT CHRONIC KIDNEY DISEASE (CKD) PATIENTS: A CASE REPORT • B. Montersino, F. Minelli, F. Leone, F. Fassio, M.M. Rossetti, L. Colla, G.B. Piccoli, R. Attini, T. Todros ABS 24. PREVALENCE SURVEY ON BREASTFEEDING AND BABIES’ HEALTH DETERMINANTS IN SICILY: RESULTS OF THE STUDY “IN PRIMIS” • M.P. Ferro, P. Ficano, B. Ottaviani, S. Palmeri, S. Scelfo, S. Colaceci, A. Cernigliaro, S. Spila Alegiani, A. Giusti, A. Casuccio, S. Scondotto; Master Prospect Working Group ABS 25. PRE-PREGNANCY BODY MASS INDEX SHIFT ACROSS GESTATION: PRIMARY EVIDENCE OF AN ASSOCIATION WITH EATING DISORDERS • A. Meneghello, F. Volpe, L. Giliberti, P. Guerrini, G. Straface, V. Zanardo ABS 26. METABOLOMICS AND INFANTS OF MOTHERS WITH GESTATIONAL DIABETES: A PRELIMINARY STUDY • E. Cossu, M. Congiu, A. Dessì, R. Pintus, V. Fanos